Tinjauan Hukum Ekonomi Syariah Terhadap Pembiayaan Dengan Akad Rahn Dalam Produk GEMAS KSPPS NURI Jatim - Mahmudi, Mohammad; mr, Jatim (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2026)
This study examines the GEMAS (Sharia Gold Pawn) product offered by KSPPS NURI East Java from the perspective of Islamic economic law. The research aims to evaluate the extent to which this financing practice complies with Sharia principles, particularly in relation to contractual structure (akad), fairness, transparency, and the avoidance of riba (usury).The study adopts a normative qualitative approach, combining a literature review with field observations conducted at several cooperative branches. The findings indicate that KSPPS NURI East Java has implemented the rahn contract in accordance with Sharia requirements. In this arrangement, the pledged gold is held strictly as collateral and is not utilized by the cooperative for any form of benefit. The institution only charges a maintenance fee that aligns with the fatwas issued by the National Sharia Council (DSN-MUI).The GEMAS product is therefore regarded as a practical financial solution that offers speed, security, and freedom from riba for cooperative members. Nevertheless, certain challenges remain, including the need to strengthen risk management mechanisms and to enhance Sharia literacy among customers. Overall, the GEMAS financing scheme demonstrates strong potential as an applicable and Sharia-compliant model of Islamic pawning that is consistent with the objectives of maqashid al-shariah.